The Plasmid Mobilome of the Model Plant-Symbiont Sinorhizobium meliloti: Coming up with New Questions and Answers - Lagares, Antonio (2014)
Rhizobia are Gram-negative Alpha- and Betaproteobacteria living in the underground that have the ability to associate with legumes for the establishment of nitrogen-fixing symbioses. Sinorhizobium meliloti in particular—the symbiont of Medicago, Melilotus, and Trigonella spp.—has for the past decades served as a model organism for investigating, at the molecular level, the biology, biochemistry, and genetics of a free-living and symbiotic soil bacterium of agricultural relevance. To date, the genomes of seven different S. meliloti strains have been fully sequenced and annotated, and several other draft genomic sequences are also available (http://www.ncbi.nlm.nih.gov/genome/genomes/1004). The vast amount of plasmid DNA that S. meliloti frequently bears (up to 45% of its total genome), the conjugative ability of some of those plasmids, and the extent of the plasmid diversity has provided researchers with an extraordinary system to investigate functional and structural plasmid molecular biology within the evolutionary context surrounding a plant-associated model bacterium. Current evidence indicates that the plasmid mobilome in S. meliloti is composed of replicons varying greatly in size and having diverse conjugative systems and properties along with different evolutionary stabilities and biological roles. While plasmids carrying symbiotic functions (pSyms) are known to have high structural stability (approaching that of chromosomes), the remaining plasmid mobilome (referred to as the non-pSym, functionally cryptic, or accessory compartment) has been shown to possess remarkable diversity and to be highly active in conjugation. In light of the modern genomic and current biochemical data on the plasmids of S. meliloti, the current article revises their main structural components, their transfer and regulatory mechanisms, and their potential as vehicles in shaping the evolution of the rhizobial genome.